USE OF HYDRODYNAMICAL THEORIES FOR DEFINITION OF PRESSURE ON THE CONTACT SURFACE OF THE TOOL - N.S. KOLEV (Advanced Engineering Research, 2007)
In the accepted model of formation of chip we were based on hydrodynamical laws, and also on reological appearances taking place during relative movement of particles of the body. Theoretical expressions for definition of pressure on a true rake of the tool were obtained.